2017
DOI: 10.1093/jscr/rjx112
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated congenital transmesenteric hernia in an adult: a case report

Abstract: Transmesenteric hernia is a rare cause of bowel obstruction and strangulation. It can be due to iatrogenic injury, trauma, inflammatory and less likely congenital. We present a case of true congenital transmesenteric hernia in a 26-year-old male with no previous surgical history or trauma. The patient presented acutely with no prior symptoms. Investigations provided limited information towards the diagnosis of the hernia, but suggestive of mid-gut volvulus. Emergency laparotomy was performed to find >75% of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“… 4 7 So, symptomatology mainly depends on the extent of complications. Presentation can be mild in noncomplicated cases and can be severe in cases of volvulus, strangulation, and ischemia, which occurs in 33% of cases 8 as our case. The mechanism of volvulus is explained by the lack of capsulation of the hernia, which allows larger loops to herniate and twist.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“… 4 7 So, symptomatology mainly depends on the extent of complications. Presentation can be mild in noncomplicated cases and can be severe in cases of volvulus, strangulation, and ischemia, which occurs in 33% of cases 8 as our case. The mechanism of volvulus is explained by the lack of capsulation of the hernia, which allows larger loops to herniate and twist.…”
Section: Discussionmentioning
confidence: 60%
“…Simple X-ray can show signs of intestinal obstruction or stacking of bowels in a specific quadrant of the abdomen. 8 Multidetector computed tomography scan is the gold standard imaging modality. Its specificity and sensitivity are 76 and 63%, respectively, with an accuracy of 77% for trans-mesenteric hernias.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the "Petersen type" involves bowel loops protruding behind the Roux limb before passing through a defect in the transverse mesocolon. Alhayo et al (2017) highlight the varied presentation of transmesenteric hernias, ranging from asymptomatic to severe cases of acute abdomen and even unexpected death. Furthermore, it has been suggested that transmesocolic hernias are more prone to complications such as volvulus, strangulation, ischemia, and perforation compared to other subtypes of internal hernias.…”
Section: Discussionmentioning
confidence: 99%
“…Bilgisayarlı tomografi (BT) bulguları ile internal herni tanımlanabilse de İTH tanısı radyolojik olarak da zordur, Bu nedenle ancak peroperatif tanı konabilen vakalar da az değildir. [6][7][8][9][10][11] Bu çalışmada 6 yaşında ileus bulguları ile gelen bir kız hastanın, peroperatif görülen İTH tablosunun cerrahi öncesi klinik seyri, cerrahi uygulaması ve ameliyat sonrası takip tecrübemizi literatür bilgileri eşliğinde sunmayı amaçladık.…”
Section: Introductionunclassified